2019
DOI: 10.3390/app9050908
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Screening System for Patient Vibration Signals with Knee Disorder

Abstract: In this paper, we introduce a simple sound signal diagnostic method to evaluate anterior cruciate ligament (ACL) injury before and after reconstructive surgery. Sixty-five recruited participants were divided into control (n = 27) and experimental (n = 38) groups. Dynamic time warping of sound signals was applied to evaluate the healthy and injured limbs before surgery with those after surgery via analysis of variance and Z-test analysis. In the control group, the average differences among three sensing points … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…An illustration in Figure 6 shows some of these wavelets along with measured waveforms. Chiu Ching Tuan et al [34] have executed dynamic time warping on the wavelet coefficients of signals from healthy patients and patients with a history of ligament injuries. They have concluded that those coefficients can represent a useful indicator of the degree of ligament stabilization during recovery [34].…”
Section: Time-frequency Domain Analysismentioning
confidence: 99%
“…An illustration in Figure 6 shows some of these wavelets along with measured waveforms. Chiu Ching Tuan et al [34] have executed dynamic time warping on the wavelet coefficients of signals from healthy patients and patients with a history of ligament injuries. They have concluded that those coefficients can represent a useful indicator of the degree of ligament stabilization during recovery [34].…”
Section: Time-frequency Domain Analysismentioning
confidence: 99%
“…The second one used the nullor grounded mirror and floating mirror elements to model the active devices that involved differential or multiple single-ended signals. Tuan et al [7] introduced a simple sound signal diagnostic method to evaluate the anterior cruciate ligament (ACL) injury before and after reconstructive surgery. Dynamic time warping of sound signals was applied to evaluate the healthy and injured limbs before surgery with those after surgery via variance analysis and Z-test analysis.…”
mentioning
confidence: 99%